PENGARUH GOOD CORPORATE GOVERNANCE DAN KINERJA KEUANGAN PERUSAHAAN TERHADAP TINGKAT KESEHATAN KEUANGAN - Sukarna, Fanny Noviyanti; Mildawati, Titik (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is meant to examine the influence of good corporate governance mechanism and financial performance of the company to the probability of financial distress in manufacturing companies which are listed in Indonesia Stock Exchange. The good corporate governance mechanism includes the board of directors, board of commissioner, managerial ownership, institutional ownership, and the size of audit committee, meanwhile the financial performance includes profitability, leverage and liquidity. This research has been carried out by using 135 sample companies. The sample collection technique has been carried out by using purposive sampling over 2010-2014 periods. The analysis data has been done by using multiple regressions analysis method.The result of this research shows that board of directors, managerial ownership, institutional owner ship, leverage and liquidity do not have any influence to the financial distress, meanwhile the board commissioner, the size of audit committee and profitability have negative influence to the financial distress.Keywords: Good Corporate Governance, Profitability, Leverage, Liquidity, Financial Distress.